Functional outcomes of the treatment of closed displaced mid-shaft clavicular fractures in adults : Comparison of the results of surgical versus conservative treatment - صالح اسامه; معن سعد; عزّة المحمد (Latakia University Journal -Medical Sciences Series, 2023)
Objective: Improving functional outcomes in adult patients with closed displaced midshaft clavicular fractures by studing the advantages and disadvantages of both treatment methods "surgical and conservative" and choice the best method of treatment. Patients and methods: Acomparative study included 47 patients over 18 years old. The patients were divided into 2 groups (surgical and conservative).DASH and MURLEY scores were performed after (6،9،12،24،52) weeks. The duration of the research was two years "2020-2021" Results: The rate of nonunion was significantly higher in the conservative treated group than in the surgical group(12.5% compared with 6.5%).DASH and MURLEY scores were significantly better for the surgical group at all follow ups. Return to work period in operative group was faster than that in nonoperative one. Conclusion: Open reduction and internal fixation for closed displaced midshaft clavicular fractures improves functional outcomes and decreases the rate of nonunion and malunion. Surgical treatment also makes return to work faster.